Pengaruh Motivasi Kerja dan Komitmen Organisasi terhadap Organizational Citizenship Behaviour (OCB) dengan Kepuasan Kerja sebagai Variabel Interverning (Studi Kasus Pada PT. Obsidian Stainless Steel Indonesia Stock Kabupaten Konawe) - Brian Tritama Haeba; Abd. Azis Muthalib; Nofal Supriaddin; Asraf Asraf (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study focuses on the influence of work motivation and organizational commitment on Organizational Citizenship Behavior (OCB) in PT. Obsidian Stainless Steel Indonesia, Konawe Regency. This research is motivated by the importance of work motivation and organizational commitment in increasing OCB which has an impact on company performance. This study aims to fill the knowledge gap regarding the relationship between work motivation, organizational commitment, and OCB with job satisfaction as an intervening variable. The methodology used in this study is a quantitative approach with Partial Least Square (PLS) analysis techniques. The main results of the study showed that work motivation had a positive and significant influence on OCB; organizational commitment also has a positive and significant effect on OCB; and job satisfaction as intervening variables strengthen the relationship between work motivation and OCB as well as organizational commitment and OCB. The study found that job satisfaction plays an important role in amplifying the influence of work motivation and organizational commitment to OCB. The implications of this study show that companies improve employee OCB